Factors and Prevention of Teenagers Social Illness in Malaysia: Reflection from Yusuf AS Character - Nurul Badriyah Ali; Syaimak Ismail; Angraini Ramli (USIM Press, 2024)
Ulum Islamiyyah The Malaysian Journal of Islamic Studies Volume 35 Issue 1 Page (37-58)